2022
DOI: 10.3390/antiox11020307
|View full text |Cite
|
Sign up to set email alerts
|

p62-Nrf2 Regulatory Loop Mediates the Anti-Pulmonary Fibrosis Effect of Bergenin

Abstract: Idiopathic pulmonary fibrosis (IPF) can severely disrupt lung function, leading to fatal consequences, and there is currently a lack of specific therapeutic drugs. Bergenin is an isocoumarin compound with lots of biological functions including antioxidant activity. This study evaluated the potential beneficial effects of bergenin on pulmonary fibrosis and investigated the possible mechanisms. We found that bergenin alleviated bleomycin-induced pulmonary fibrosis by relieving oxidative stress, reducing the depo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Furthermore, the in vivo study employed with SQSTM1 cKO mice confirmed that SQSTM1 in tubular cells played a critical role in the protective effect of Cana on renal fibrosis. Notably, SQSTM1 can contribute to the regulation of fibrotic process via the vitamin D receptor or NRF2 pathway, which are independent autophagy programs ( 65 , 66 ). Thus, the role of SQSTM1 in regulating the protective effects of Cana in renal fibrosis may be either dependent or independent of the autophagy pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the in vivo study employed with SQSTM1 cKO mice confirmed that SQSTM1 in tubular cells played a critical role in the protective effect of Cana on renal fibrosis. Notably, SQSTM1 can contribute to the regulation of fibrotic process via the vitamin D receptor or NRF2 pathway, which are independent autophagy programs ( 65 , 66 ). Thus, the role of SQSTM1 in regulating the protective effects of Cana in renal fibrosis may be either dependent or independent of the autophagy pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Nrf2 is the master activator for most of the antioxidant enzymes, and its expression was lower in the fibroblasts and myofibroblasts of patients with IPF [ 29 ]. Bergenin improve pulmonary fibrosis by inducing the activation of Nrf2 to relieve oxidative stress and reduce the deposition of the extracellular matrix [ 30 ]. Some studies indicated that CA showed good capability against oxidative stress [ 31 ], which protected cells from injury.…”
Section: Discussionmentioning
confidence: 99%
“…NA1-115-7 is the latest type of selective Mcl-1 inhibitor that specifically induces apoptosis in Mcl-1-dependent tumor cells, and two hours of treatment is sufficient to trigger cell death [ 9 ]. Natural products with high bioactivity and low toxicity have been widely used in tumor therapy research [ 47 ]. Both Allyl isothiocyanate [ 48 ] and Pyrethrum extract [ 49 ] weere found to have a role in regulating Mcl-1 levels, but the exact mechanism remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%